1991
DOI: 10.1002/ijc.2910480307
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable and fruit consumption and cancer risk

Abstract: The relationship between cancer risk and frequency of consumption of green vegetables and fruit has been analyzed using data from an integrated series of case-control studies conducted in northern Italy between 1983 and 1990. The overall dataset included the following histologically confirmed cancers: oral cavity and pharynx, 119; oesophagus, 294; stomach, 564; colon, 673; rectum, 406; liver, 258; gall-bladder, 41; pancreas, 303; larynx, 149; breast, 2,860; endometrium, 567; ovary, 742; prostate, 107; bladder,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
127
1
5

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(139 citation statements)
references
References 18 publications
(13 reference statements)
6
127
1
5
Order By: Relevance
“…Epidemiological studies indicate an inverse correlation between the intake of polyphenols and the incidence of chronic diseases, such as cardiovascular disease (CVD) and cancer (Negri et al, 1991;Hertog et al, 1993;Keli et al, 1996). Fruits and vegetables rich in polyphenols have been expected to be important materials for the maintenance of health.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies indicate an inverse correlation between the intake of polyphenols and the incidence of chronic diseases, such as cardiovascular disease (CVD) and cancer (Negri et al, 1991;Hertog et al, 1993;Keli et al, 1996). Fruits and vegetables rich in polyphenols have been expected to be important materials for the maintenance of health.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, convincing evidence for a protective role of these dietary components in cancer development is lacking for most malignancies, including RCC. 6 A number of case-control studies have reported an inverse association between intake of either fruits or vegetables and RCC risk, [7][8][9][10][11] while some investigations failed to demonstrate any significant association. [12][13][14] More importantly, data from prospective studies remain sparse and largely non-conclusive.…”
mentioning
confidence: 99%
“…With respect to bladder cancer, most epidemiological studies support a possible protective effect of vegetable (Bruemmer et al, 1996;D'Avanzo et al, 1995;Michaud et al, 1999;Mills et al, 1991;Negri et al, 1991) and fruit consumption (Bruemmer et al, 1996;Chyou et al, 1993;Negri et al, 1991;Shibata et al, 1992), although some studies have reported no association for vegetable (Riboli et al, 1991;Shibata et al, 1992) or fruit consumption (Michaud et al, 1999;Riboli et al, 1991). There are many candidate agents in fruits and vegetables that influence bladder cancer risk, including carotenoids, vitamin C, vitamin E, and folate.…”
mentioning
confidence: 99%